Reg3G gene expression in regenerating skeletal muscle and corresponding nerve. Issue 1 (5th December 2013) - Klasan, Gordana Starcevic; Ivanac, Danijel; Erzen, Dubravka Jurisic; Picard, Anne; Takasawa, Shin; Peharec, Stanislav; Arbanas, Juraj; Girotto, Dean; Jerkovic, Romana
ABSTRACT Introduction: The Reg genes play a major role in the regeneration of various tissues; however, no reports have been published regarding expression of the Reg3G gene in skeletal muscle. In this study we investigated the expression of the Reg3G gene in regeneration of rat skeletal muscle and injured nerves. Methods: We used 3 experimental models of muscle and nerve injury. RT‐PCR and Western blot analysis were performed for detection of Reg3G in regenerating muscle and nerve. Results: We found transcriptional activation of the Reg3G gene in the soleus and extensor digitorum longus muscles and in their corresponding nerves after both muscle and nerve injury in different time periods, respectively. Conclusions: The results suggest that the Reg3G gene plays a major role in communication between injured axons and muscle and may play a significant role in skeletal muscle and peripheral nerve regeneration. Muscle Nerve49: 61–68, 2014